KEDUDUKAN HUKUM ANGKUTAN PRIBADI YANG DIPERGUANKAN SEBAGAI ANGKUTAN UMUM BERDASARKAN UNDANG-UDNANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Agus Mahayana, A. A. Gede; Ariani, I Gusti Ayu Agung (Kertha Wicara : Journal Ilmu Hukum, 2015)
Transportation and transport are very important field of activity in social life in Indonesia. Transportation is divided into two, the first public transportation (paratransit) is a transport which does not have fixed routes and schedules in its operation along its route and the second one (mass transit) is a transport that has a fixed route and schedule and keeps a clear stoppage. However, it is not infrequently a problem arising in the transportation, one of them is the legal standing. Therefore, in this paper it will be discussed how the legal standing of private motor vehicles used as public transport and how legal sanctions against the use of private cars as public transport in violating Law No. 22 of 2009 on Road Traffic and Transport.
Keywords: Transportation, Motor Vehicle, Public Transport, Legal Standing